1974
DOI: 10.1017/s0022172400023603
|View full text |Cite
|
Sign up to set email alerts
|

The growth of salmonellas on cooked cured pork

Abstract: SUMMARYWith the use of streptomycin-resistant mutants to facilitate recovery, 5 strains of 4 species ofSalmonellawere shown to grow rapidly at 22° C. on low salt ham even from an inoculum of 10–20 organisms.S. pullorumdid not grow well. All 6 strains ofSalmonellasurvived but did not grow on ‘high salt ham’. We conclude that cooked ham containing approximately 2·8 g. NaCl/100 g. H2O once infected is more likely to give rise to food poisoning than is ham with the higher salt content traditionally used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1994
1994
1998
1998

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…At 37°C this effect was noted at above 3% added NaCI; growth was unaffected between 0 and 3% added NaCI. Akman and Park (1974) presented growth data for Salm. enteritidis in nutrient broth containing various concentrations of NaCl at 22°C.…”
Section: Growth Of Microcoloniesmentioning
confidence: 99%
See 1 more Smart Citation
“…At 37°C this effect was noted at above 3% added NaCI; growth was unaffected between 0 and 3% added NaCI. Akman and Park (1974) presented growth data for Salm. enteritidis in nutrient broth containing various concentrations of NaCl at 22°C.…”
Section: Growth Of Microcoloniesmentioning
confidence: 99%
“…However, the effect of decreasing p with increasing [NaCl]/decreasing a , , observed by both Matches and Liston (1972) and Li and Torres (1993), was not noted in the present study, although the results presented here support their findings that the lag phase was increased. Akman and Park (1974) also studied the growth of six strains of Salmonella on cooked cured pork at 22°C. The authors reported rapid growth of Salm.…”
Section: Growth Of Microcoloniesmentioning
confidence: 99%